Sexual spores in edible mushroom: bioactive components, discharge mechanisms and effects on fruiting bodies quality - Yunting Li; Yao Feng; Yuling Shang; Heran Xu; Rongrong Xia; Zhenshan Hou; Song Pan; Li Li; Yuanyuan Bian; Jiayi Zhu; Zijian Wang; Guang Xin (Food Science and Human Wellness)
Edible mushroom sexual spores have been gaining more interest due to their bioactive components and functions. Spore discharge (SD) is an important factor affecting the quality of edible mushrooms.In this review, the bioactive nutrients of sexual spores of edible mushrooms were summarized, the SD mechanism was described, and the relationship between postharvest SD and the quality of edible mushrooms was analyzed.Spores contain various bioactive nutrients that are beneficial to the human body. Mature mushrooms can actively discharge spores in a process affected by light, relative humidity, and temperature. During storage, the physiological metabolism of spore-bearing gill tissue is vigorous, promoting the release of postharvest spores and changing the nutritional value of fruiting bodies. The flavor of the fruiting bodies also varied significantly during SD. Edible mushroom sexual spores have the potential to become new raw materials for functional food and medical resources. Research on the effect of the mechanism of SD on the quality of edible mushrooms and the development of SD regulation technology may be a new trend in the quality control of edible mushrooms, which will promote the development of the edible mushroom industry.